Congenital Rectal Atresia with Rectovestibular Fistula: A Case Report - Ghabisha, Saif; Ahmed, Faisal; Al-wageeh, Saleh; Al-shami, Ebrahim; Al-naggar, Khalil; Obaid, Ghamdan; Alfaragi , Mohammed (International Journal of Scientific Research and Management (IJSRM), 2021)
Within the spectrum of anorectal malformations, congenital rectal atresia associated with rectovestibular fistulas is an uncommon and curable entity. It has been reported to have a prevalence of less than 1%. In this study, we report a 9-month-old female presented with the passing of feces and gas through the small orifice of the vaginal wall. The diagnosis of congenital rectal atresia associated with rectovestibular fistula was confirmed by radiological investigations. The patient was successfully treated with transfistula anorectoplasty. Here we present the case, management approach, and a review of the previous literatures.